2000
DOI: 10.1002/1098-2329(200023)19:3<210::aid-adv6>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Swelling behavior of poly(N-vinyl-2-pyrrolidone) and poly(N-vinyl-2-pyrrolidone)/K2S2O8 hydrogels in urea solutions

Abstract: Hydrogels with varying cross‐linking densities and average molecular weights between two consecutive cross‐links were prepared from the binary poly(N‐vinyl‐2‐pyrrolidone)/water and ternary poly(N‐vinyl‐2‐pyrrolidone)/water/K2S2O8 systems by irradiation with γ rays at ambient temperature. Both hydrogel systems were employed for diffusion and swelling experiments in various urea solutions at room temperature. Diffusion of urea solutions into hydrogels has been found to be of the non‐Fickian type, except for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Figure 7 shows the swelling results for each system after reaching equilibrium in water (48 h of immersion; measurements corresponding to 2 and 24 h of swelling are shown in Table S1). The materials prepared in this study showed good degrees of swelling, in the order of values typically reported in the literature 60–62 …”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Figure 7 shows the swelling results for each system after reaching equilibrium in water (48 h of immersion; measurements corresponding to 2 and 24 h of swelling are shown in Table S1). The materials prepared in this study showed good degrees of swelling, in the order of values typically reported in the literature 60–62 …”
Section: Resultssupporting
confidence: 71%
“…The materials prepared in this study showed good degrees of swelling, in the order of values typically reported in the literature. [60][61][62] Some results deserve to be remarked. First, the increase in PVP concentration does not influence (within the limits of error) the degree of swelling of the gels, with both G8 and G16 reaching values of approximately 1100%.…”
Section: Swelling Capacitymentioning
confidence: 99%